A method for enhancing the interfacial compatibility of basalt fiber aerogel

By preparing a specific interface modifier on the basalt fiber and depositing a titanium dioxide layer, the problem of weak interface structure between the fiber and aerogel is solved, and the mechanical and thermal insulation properties of the composite material are significantly improved.

CN118754482BActive Publication Date: 2025-01-21SOUTHWEST TECHNICAL ENGINEERING RESEARCH INSTITUTE OF CHINA SOUTH IND GROUP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411028056.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-30
Publication Date
2025-01-21
Estimated Expiration
2044-07-30

AI Technical Summary

Technical Problem

In the prior art, the interface structure between silica aerogel and fiber is weak, and cracks are prone to spread under external forces, and fibers and aerogel matrix are separated, resulting in interface failure and degradation of composite material properties.

Method used

By preparing a specific interface modifier and using it to modify basalt fibers, combined with magnetron sputtering technology, a titanium dioxide layer is deposited to enhance the compatibility and connection strength of the fiber surface.

Benefits of technology

It effectively improves the interface compatibility between basalt fiber and silica aerogel, improves the mechanical properties and thermal insulation properties of the composite material, delays fiber erosion, and improves alkali resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118754482B_ABST
    Figure CN118754482B_ABST
Patent Text Reader

Abstract

The present invention provides a method for enhancing the interfacial compatibility of basalt fiber aerogel, which relates to the field of inorganic non-metallic materials, including: step 1, preparation of interfacial modifier: preparing interfacial modifier by solvent of anhydrous ethanol and deionized water, maleic anhydride, long-chain diaminosilane coupling agent, silane coupling agent KH550; step 2, modification of basalt fiber: modifying basalt fiber by interfacial modifier; step 3, magnetron sputtering: coating the surface of modified basalt fiber with magnetron sputtering layer by magnetron sputtering TiO2. The method can effectively improve the interfacial compatibility between basalt fiber and silica aerogel, thereby obtaining a composite material with strong interfacial bonding force, good corrosion resistance, no pollution and excellent performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of inorganic non-metallic materials, and in particular to a method for enhancing the interface compatibility of basalt fiber aerogel. Background Art

[0002] The performance of fiber-reinforced composites mainly depends on three components, including matrix, fiber and interface. Although the performance of matrix and fiber directly determines the overall performance of the composite, the interface can limit the stress transfer between fiber and matrix and avoid shedding between matrix and fiber, which directly affects the stability of the composite and plays an important role in the failure process of the composite.

[0003] The network structure of silica aerogel is a three-dimensional polycondensate connected by silicon-oxygen bonds. Such a structure has extremely high porosity and small pore size, which can effectively limit the solid conduction and gaseous heat conduction of heat flow, and is an excellent thermal insulation material; however, the weak strain of the silicon-oxygen covalent bond itself causes high-purity silica to have the characteristics of low strength, poor toughness, and unstable mechanical structure, resulting in high-purity silica aerogel cannot be directly applied, and usually needs to be compounded with high-strength and toughness materials. At present, the existing technology effectively improves the mechanical properties of aerogel by adding fiber reinforcement materials and compounding with silica aerogel; however, due to the ultra-high porosity of silica aerogel and the smooth surface of the fiber, the interface structure between the aerogel and the fiber is relatively weak. Under the action of external force, the cracks between the interfaces are very easy to propagate along the interface, resulting in debonding or detachment between the fiber and the aerogel matrix, and even interface failure. Once the interface fails, the stress loaded on the aerogel cannot be transferred to the fiber, which leads to the fracture of the aerogel. Therefore, improving the interfacial compatibility between fiber and aerogel is of great significance to the promotion and application of fiber-aerogel composites. Summary of the invention

[0004] In view of the problems existing in the above prior art, the purpose of the present invention is to provide a method for enhancing the interface compatibility of basalt fiber aerogel, which can effectively improve the interface compatibility between fiber and aerogel, thereby obtaining a composite material with strong interface bonding, good corrosion resistance, no pollution and excellent performance.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] A method for enhancing the interfacial compatibility of basalt fiber aerogel, comprising:

[0007] Step 1, preparation of interface modifier: First, anhydrous ethanol and deionized water are mixed to obtain a modified solvent, then maleic anhydride, long-chain diaminosilane coupling agent (chemical formula NH2(CH2)2NH(CH2)3Si(OCH3)3) and silane coupling agent KH550 (chemical formula NH2CH2CH2CH2Si(OC2H5)3) are weighed respectively, and the modified solvent is slowly added dropwise under vigorous stirring. After the addition is completed, stirring is continued for 20 to 40 minutes until there is no obvious oily substance, thereby obtaining an interface modifier;

[0008] Step 2, basalt fiber modification: First, basalt is uniformly mixed in a high-speed mixer, and basalt fiber precursor is produced on an extruder with a length / diameter ratio of 40 to 45; then, after the extruded basalt fiber precursor is cooled, it is immersed in an interface modifier for modification; then, the modified basalt fiber precursor is bundled and wound by an automatic winding machine; finally, the bundled and wound fiber precursor is dried at room temperature and then placed in an oven for drying;

[0009] Step 3, magnetron sputtering: First, the modified basalt fiber in step 2 is placed in the vacuum chamber of the magnetron sputtering equipment, the magnetron sputtering target is TiO2, and the vacuum is evacuated; then, argon gas is introduced into the vacuum chamber, and the magnetron sputtering equipment is turned on for magnetron sputtering; finally, after the magnetron sputtering is completed, the fiber after magnetron sputtering is removed and stored in an oven.

[0010] Based on further optimization of the above scheme, the volume ratio of maleic anhydride, long-chain diaminosilane coupling agent, silane coupling agent KH550, and modified solvent is 1.5-2.5:1-2:1-2:98-102.

[0011] Firstly, the silanol groups produced by hydrolysis of a specific formula of the interface modifier are fully condensed with the silanol groups on the surface of the basalt fiber on the basis of forming hydrogen bonds, thereby ensuring that the interface modifier is evenly and firmly attached to the surface of the basalt fiber; then, the titanium dioxide layer is prepared by magnetron sputtering, and the titanium dioxide is pulled by a large number of polar covalent bonds produced during the condensation of the interface modifier and bonded by van der Waals force, thereby effectively enhancing the compatibility of the titanium dioxide sputtered layer and the surface of the basalt fiber; at the same time, the titanium dioxide is pulled by the fully condensed interface modifier during magnetron sputtering, effectively ensuring the dispersion of titanium dioxide on the surface of the basalt fiber and reducing titanium dioxide agglomerates, thereby improving the density of the titanium dioxide coating layer, and enhancing the fluidity of the solution on the surface of the basalt fiber. When it is subsequently compounded with silica aerogel, as the porosity of the silica aerogel increases, the contact surface between the coating layer and the aerogel pores is increased by the fluidity of the solution, thereby improving the interface compatibility between the aerogel and the fiber. In addition, by magnetron sputtering of titanium dioxide, Ti 4+It enters the network structure of the fiber surface in the form of tetracoordinate (TiO4). During the composite process with aerogel, it can form a mixed skeleton of titanosilicate with SiO2, which not only strengthens the network structure of the fiber, but also improves the connection strength between the fiber structure and the aerogel, thereby improving the tensile strength. In addition, the dense titanium dioxide coating can delay the erosion of basalt fiber, generating Ti(OH)4 layered on the fiber surface during the corrosion process, thereby reacting with Ti 4+ The combined effect enhances the fiber polymerization degree and effectively improves the alkali resistance of basalt fiber.

[0012] Based on further optimization of the above scheme, the volume ratio between anhydrous ethanol and deionized water in step 1 is 1:1.

[0013] Based on further optimization of the above scheme, the extrusion temperature of the extruder in step 2 is 180-220° C., and the extrusion speed is 90-110 rpm.

[0014] Based on further optimization of the above scheme, in step 2, the basalt fiber is immersed in the interface modifier for 25 to 35 minutes.

[0015] Based on further optimization of the above scheme, the drying temperature of the oven in step 2 is 90-100° C., and the drying time is 8-10 hours.

[0016] Based on the further optimization of the above scheme, the vacuum degree in step 3 is 3x10 -3 ~5x10 -3 Pa, substrate temperature is 200~500℃, bias voltage is -100~-200V; magnetron sputtering parameters are: target sputtering power is 50~120W, working gas pressure is 0.25~0.5Pa, sputtering time is 30~40min.

[0017] Based on further optimization of the above scheme, the oven storage time in step three is 8 to 12 hours, and the storage temperature is 30 to 50°C.

[0018] Based on the further optimization of the above scheme, after step 3, the interface-modified basalt fiber and the silica aerogel are further compounded, specifically:

[0019] First, take ethyl orthosilicate, ethanol and deionized water in a stirring bottle and stir them thoroughly to obtain a mixed solution, and then use hydrochloric acid to adjust the pH of the mixed solution to 1-2; then, weave the modified basalt fibers in step three and lay them in layers, add the laid basalt fibers into the mixed solution adjusted to an acidic environment, adjust the temperature to 43-47°C, react for 0.8-1.5h, and then adjust the pH to 7-8 with ammonia water to obtain a composite material wet gel; finally, pour the composite material wet gel into a mold, perform pressure filtration (at normal pressure) through a vacuum-assisted system, and then perform aging and drying to obtain a basalt fiber aerogel composite material.

[0020] Based on further optimization of the above scheme, the volume ratio of tetraethyl orthosilicate, ethanol and deionized water is 2.8-3.2:2.1-2.5:0.1.

[0021] Based on further optimization of the above scheme, the ratio of the basalt fiber to the mixed solution is: 0.1-0.2 g: 35-45 ml.

[0022] Based on further optimization of the above solution, the weaving method of the single layer of basalt fiber is that the warp yarns and the weft yarns are interlaced and wound.

[0023] Based on further optimization of the above scheme, the concentration of hydrochloric acid is 0.05-0.15 mol / L, and the concentration of ammonia water is 0.1 mol / L.

[0024] Based on further optimization of the above scheme, the aging treatment process is: first, aging in anhydrous ethanol at a temperature of 55-65°C for 1.5-2.5 days; then, aging in an aging liquid at room temperature for 1.5-2.5 days; wherein the aging liquid includes trimethylchlorosilane, anhydrous ethanol and n-hexane, and their volume ratio is 8-12:10:48-52.

[0025] The following are the effects of the technical solution of the present invention:

[0026] The present application combines basalt fiber interface modification with magnetron sputtering deposition of titanium dioxide, and utilizes the synergistic effect between a specific interface modifier and titanium dioxide to effectively improve the interface compatibility between basalt fiber and silica aerogel, thereby ensuring sufficient and uniform contact between basalt fiber and silica aerogel, and avoiding problems such as interface crack expansion, fiber and aerogel matrix separation, and composite material performance failure caused by the ultra-high porosity of silica aerogel and the smooth surface of basalt fiber, thereby ensuring that the basalt fiber aerogel composite material has good mechanical properties, high thermal insulation properties, and stable long-term performance; at the same time, the method of the present application does not generate three wastes during the preparation of the basalt fiber aerogel composite material, is highly environmentally friendly, has simple preparation process steps, and readily available raw materials, and can be used for large-scale industrial production with low production costs.

[0027] Compared with the basalt fiber aerogel in the prior art, the thermal conductivity of the basalt fiber aerogel composite material prepared in the present application is reduced by more than 20%, and the mechanical properties are improved by more than 15%, and it has excellent mechanical properties and thermal insulation properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The figure is a flow chart of the surface modification of basalt fiber in an embodiment of the present invention.

[0029] Figure 2 is a SEM image of basalt fiber in an embodiment of the present invention; wherein, Figure 2 (a) is the surface image of basalt fiber without magnetron sputtering. Figure 2 (b) is the surface image of basalt fiber after magnetron sputtering. Figure 2 (c) is the corrosion pit image of basalt fiber after magnetron sputtering.

[0030] Figure 3 Schematic diagram of the weaving structure of basalt fiber in an embodiment of the present invention.

[0031] Among them, 10. unmodified fiber; 20. interface modifier; 30. modified fiber; 40. automatic winding machine. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0033] Embodiment 1:

[0034] A method for enhancing the interfacial compatibility of basalt fiber aerogel, comprising:

[0035] Step 1, preparation of interface modifier: First, anhydrous ethanol and deionized water are mixed in a volume ratio of 1:1 to obtain a modified solvent; then, maleic anhydride (maleic anhydride commonly used in the art can be used), long-chain diaminosilane coupling agent (chemical formula NH2(CH2)2NH(CH2)3Si(OCH3)3, product purity is stable at more than 99%) and silane coupling agent KH550 (chemical formula NH2CH2CH2CH2Si(OC2H5)3, product purity is stable at more than 99%) are weighed respectively, and the modified solvent is slowly added dropwise under vigorous stirring (the stirring speed is determined according to the actual situation, generally 80r / min), wherein the volume ratio of maleic anhydride, long-chain diaminosilane coupling agent, silane coupling agent KH550 and modified solvent is 1.5:1:1:98. After the addition is completed, stirring is continued for 20 minutes until there is no obvious oily substance, thereby obtaining an interface modifier.

[0036] Step 2: Modification of basalt fiber: First, basalt is uniformly mixed in a high-speed mixer (stirring speed is generally 800r / min), and basalt fiber precursor is produced on an extruder with a length / diameter ratio of 40, the extrusion temperature is 180℃, and the extrusion speed is 90rpm; then, after the extruded basalt fiber precursor is cooled (it can be cooled by cold water or other methods, which can be set according to actual conditions), it is immersed in an interface modifier for 25min for modification; then, the modified basalt fiber precursor is bundled and wound by an automatic winding machine. For details of the modification process, see Figure 1 As shown; finally, the bundled and wound fiber filaments are dried at room temperature and then placed in an oven for drying. The drying temperature of the oven is 90°C and the drying time is 8 hours.

[0037] Step 3: Magnetron sputtering: First, place the modified basalt fiber in step 2 into the vacuum chamber of the magnetron sputtering equipment. The magnetron sputtering target is TiO2. Vacuum the chamber to a vacuum degree of 3x10 -3 Pa; then, argon gas was introduced into the vacuum chamber, and the magnetron sputtering equipment was turned on for magnetron sputtering, wherein the substrate temperature was 200°C, the bias voltage was -100V, and the magnetron sputtering parameters were: target sputtering power 50W, working gas pressure 0.25Pa, and sputtering time 30min; finally, the magnetron sputtering was completed, and the fibers after magnetron sputtering were removed and stored in an oven for 8h at a storage temperature of 30°C.

[0038] Step 4: Composite of interface modified basalt fiber and silica aerogel:

[0039] First, tetraethyl orthosilicate, ethanol and deionized water are fully stirred in a stirring bottle to obtain a mixed solution, wherein the volume ratio of tetraethyl orthosilicate, ethanol and deionized water is 2.8:2.1:0.1, and then hydrochloric acid is used to adjust the pH of the mixed solution to 2, and the concentration of hydrochloric acid is 0.05 mol / L; then, the modified basalt fiber in step 3 is woven and layered, and the weaving method of the single layer of basalt fiber is that the warp yarn and the weft yarn are interlaced (such as Figure 3 As shown), the stacked basalt fibers are added to a mixed solution adjusted to an acidic environment, the ratio of basalt fiber to the mixed solution is: 0.1g:35ml, the temperature is adjusted to 43°C, and after reacting for 0.8h, the pH is adjusted to 7 with ammonia water, and the concentration of ammonia water is 0.1mol / L to obtain a composite material wet gel; finally, the composite material wet gel is poured into a mold, pressure filtered (pressure is normal pressure) through a vacuum-assisted system, and then aged and dried, wherein the aging process is specifically as follows: first, aging in anhydrous ethanol at a temperature of 55°C for 2.5 days; then, aging in an aging solution at room temperature for 2.5 days; wherein the aging solution includes trimethylchlorosilane, anhydrous ethanol and n-hexane, and their volume ratio is 8:10:48, and the drying process can adopt a conventional drying process in the art, which is not specifically limited in this embodiment, to obtain a basalt fiber aerogel composite material.

[0040] Embodiment 2:

[0041] A method for enhancing the interfacial compatibility of basalt fiber aerogel, comprising:

[0042] Step 1, preparation of interface modifier: First, anhydrous ethanol and deionized water are mixed in a volume ratio of 1:1 to obtain a modified solvent; then, maleic anhydride (maleic anhydride commonly used in the art can be used), long-chain diaminosilane coupling agent (chemical formula NH2(CH2)2NH(CH2)3Si(OCH3)3, product purity is stable at more than 99%) and silane coupling agent KH550 (chemical formula NH2CH2CH2CH2Si(OC2H5)3, product purity is stable at more than 99%) are weighed respectively, and the modified solvent is slowly added dropwise under vigorous stirring (the stirring speed is determined according to the actual situation, generally 100r / min), wherein the volume ratio of maleic anhydride, long-chain diaminosilane coupling agent, silane coupling agent KH550 and modified solvent is 2:1.5:1.5:100. After the addition is completed, stirring is continued for 30 minutes until there is no obvious oily substance, thereby obtaining an interface modifier.

[0043] Step 2: Modification of basalt fiber: First, basalt is uniformly mixed in a high-speed mixer (stirring speed is generally 900r / min), and basalt fiber precursor is produced on an extruder with a length / diameter ratio of 43, the extrusion temperature is 200℃, and the extrusion speed is 100rpm; then, after the extruded basalt fiber precursor is cooled (it can be cooled by cold water or other methods, which can be set according to actual conditions), it is immersed in an interface modifier for 30 minutes for modification; then, the modified basalt fiber precursor is bundled and wound by an automatic winding machine. For details of the modification process, see Figure 1 As shown; finally, the bundled and wound fiber filaments are dried at room temperature and then placed in an oven for drying. The drying temperature of the oven is 95°C and the drying time is 9h.

[0044] Step 3: Magnetron sputtering: First, place the modified basalt fiber in step 2 into the vacuum chamber of the magnetron sputtering equipment. The magnetron sputtering target is TiO2. Vacuum the chamber to a vacuum degree of 4x10 -3 Pa; then, argon gas was introduced into the vacuum chamber, and the magnetron sputtering equipment was turned on for magnetron sputtering, wherein the substrate temperature was 350°C, the bias voltage was -150V, and the magnetron sputtering parameters were: target sputtering power 85W, working gas pressure 0.35Pa, and sputtering time 35min; finally, the magnetron sputtering was completed, and the fibers after magnetron sputtering were removed and stored in an oven for 10h at a storage temperature of 40°C.

[0045] Step 4: Composite of interface modified basalt fiber and silica aerogel:

[0046] First, tetraethyl orthosilicate, ethanol and deionized water are fully stirred in a stirring bottle to obtain a mixed solution, wherein the volume ratio of tetraethyl orthosilicate, ethanol and deionized water is 3:2.3:0.1, and then hydrochloric acid is used to adjust the pH of the mixed solution to 1, and the concentration of hydrochloric acid is 0.15 mol / L; then, the modified basalt fiber in step 3 is woven and layered, and the weaving method of the single layer of basalt fiber is that the warp yarn and the weft yarn are interlaced (such as Figure 3As shown), the stacked basalt fibers are added to a mixed solution adjusted to an acidic environment, the ratio of basalt fiber to the mixed solution is: 0.15g:40ml, the temperature is adjusted to 45°C, and after reacting for 1.2h, the pH is adjusted to 8 with ammonia water, and the concentration of ammonia water is 0.1mol / L to obtain a composite material wet gel; finally, the composite material wet gel is poured into a mold, pressure filtered (at normal pressure) through a vacuum-assisted system, and then aged and dried, wherein the aging process is specifically as follows: first, aging in anhydrous ethanol at a temperature of 60°C for 2 days; then, aging in an aging solution at room temperature for 2 days; wherein the aging solution includes trimethylchlorosilane, anhydrous ethanol and n-hexane, and their volume ratio is 10:10:50, and the drying process can adopt a conventional drying process in the art, which is not specifically limited in this embodiment, to obtain a basalt fiber aerogel composite material.

[0047] Embodiment 3:

[0048] A method for enhancing the interfacial compatibility of basalt fiber aerogel, comprising:

[0049] Step 1, preparation of interface modifier: First, anhydrous ethanol and deionized water are mixed in a volume ratio of 1:1 to obtain a modified solvent; then, maleic anhydride (maleic anhydride commonly used in the art can be used), long-chain diaminosilane coupling agent (chemical formula NH2(CH2)2NH(CH2)3Si(OCH3)3, product purity is stable at more than 99%) and silane coupling agent KH550 (chemical formula NH2CH2CH2CH2Si(OC2H5)3, product purity is stable at more than 99%) are weighed respectively, and the modified solvent is slowly added dropwise under vigorous stirring (the stirring speed is determined according to the actual situation, generally 120r / min), wherein the volume ratio of maleic anhydride, long-chain diaminosilane coupling agent, silane coupling agent KH550 and modified solvent is 2.5:2:2:102. After the addition is completed, stirring is continued for 40 minutes until there is no obvious oily substance, thereby obtaining an interface modifier.

[0050] Step 2: Modification of basalt fiber: First, basalt is uniformly mixed in a high-speed mixer (stirring speed is generally 1000r / min), and basalt fiber precursor is produced on an extruder with a length / diameter ratio of 45, the extrusion temperature is 220℃, and the extrusion speed is 110rpm; then, after the extruded basalt fiber precursor is cooled (it can be cooled by cold water or other methods, which can be set according to actual conditions), it is immersed in an interface modifier for 35min for modification; then, the modified basalt fiber precursor is bundled and wound by an automatic winding machine. For details of the modification process, see Figure 1As shown; finally, the bundled and wound fiber filaments are dried at room temperature and then placed in an oven for drying. The drying temperature of the oven is 100°C and the drying time is 10 hours.

[0051] Step 3: Magnetron sputtering: First, place the modified basalt fiber in step 2 into the vacuum chamber of the magnetron sputtering equipment. The magnetron sputtering target is TiO2. Vacuum the chamber to a vacuum degree of 5x10 -3 Pa; then, argon gas was introduced into the vacuum chamber, and the magnetron sputtering equipment was turned on for magnetron sputtering, wherein the substrate temperature was 500°C, the bias voltage was -200V, and the magnetron sputtering parameters were: target sputtering power 120W, working gas pressure 0.5Pa, and sputtering time 40min; finally, the magnetron sputtering was completed, and the fibers after magnetron sputtering were removed and stored in an oven for 12h at a storage temperature of 50°C.

[0052] Step 4: Composite of interface modified basalt fiber and silica aerogel:

[0053] First, tetraethyl orthosilicate, ethanol and deionized water are fully stirred in a stirring bottle to obtain a mixed solution, wherein the volume ratio of tetraethyl orthosilicate, ethanol and deionized water is 3.2:2.5:0.1, and then hydrochloric acid is used to adjust the pH of the mixed solution to 1, and the concentration of hydrochloric acid is 0.15 mol / L; then, the modified basalt fiber in step 3 is woven and layered, and the weaving method of the single layer of basalt fiber is that the warp yarn and the weft yarn are interlaced (such as Figure 3 As shown), the stacked basalt fibers are added to a mixed solution adjusted to an acidic environment, the ratio of basalt fiber to the mixed solution is: 0.2g:45ml, the temperature is adjusted to 47°C, and after reacting for 1.5h, the pH is adjusted to 7 with ammonia water, and the concentration of ammonia water is 0.1mol / L to obtain a composite material wet gel; finally, the composite material wet gel is poured into a mold, pressure filtered (at normal pressure) through a vacuum-assisted system, and then aged and dried, wherein the aging process is specifically as follows: first, aging in anhydrous ethanol at a temperature of 65°C for 1.5 days; then, aging in an aging solution at room temperature for 1.5 days; wherein the aging solution includes trimethylchlorosilane, anhydrous ethanol and n-hexane, and their volume ratio is 12:10:52, and the drying process can adopt a conventional drying process in the art, which is not specifically limited in this embodiment, to obtain a basalt fiber aerogel composite material.

[0054] Comparative Example 1:

[0055] A method for enhancing the interfacial compatibility of basalt fiber aerogel, comprising:

[0056] Step 1, preparation of interface modifier: First, anhydrous ethanol and deionized water are mixed in a volume ratio of 1:1 to obtain a modified solvent; then, maleic anhydride (common maleic anhydride in the art can be used) and silane coupling agent KH550 (chemical formula NH2CH2CH2CH2Si(OC2H5)3, product purity is stable at more than 99%) are weighed respectively, and the modified solvent is slowly added dropwise under vigorous stirring (the stirring speed is determined according to actual conditions, generally 100r / min), wherein the volume ratio of maleic anhydride, silane coupling agent KH550, and modified solvent is 2:1.5:100. After the addition is completed, stirring is continued for 30 minutes until there is no obvious oily substance to obtain an interface modifier.

[0057] Step 2: Basalt fiber modification: the same as the steps in Example 2.

[0058] Step 3: Magnetron sputtering: the same as the steps in Example 2.

[0059] Step 4: Composite of interface-modified basalt fiber and silica aerogel: the same as the steps in Example 2.

[0060] Comparative Example 2:

[0061] A method for enhancing the interfacial compatibility of basalt fiber aerogel, comprising:

[0062] Step 1, preparation of interface modifier: First, anhydrous ethanol and deionized water are mixed in a volume ratio of 1:1 to obtain a modified solvent; then, maleic anhydride (maleic anhydride commonly used in the art can be used), long-chain diaminosilane coupling agent (chemical formula NH2(CH2)2NH(CH2)3Si(OCH3)3, product purity is stable at more than 99%) and silane coupling agent KH560 (chemical formula CH2CH(O)CH2O(CH2)3Si(OCH3)3, product purity is stable at more than 99%) are weighed respectively, and the modified solvent is slowly added dropwise under vigorous stirring (the stirring speed is determined according to the actual situation, generally 100r / min), wherein the volume ratio of maleic anhydride, long-chain diaminosilane coupling agent, silane coupling agent KH560, and modified solvent is 2:1.5:1.5:100. After the addition is completed, stirring is continued for 30 minutes until there is no obvious oily substance, thereby obtaining an interface modifier.

[0063] Step 2: Basalt fiber modification: the same as the steps in Example 2.

[0064] Step 3: Magnetron sputtering: the same as the steps in Example 2.

[0065] Step 4: Composite of interface-modified basalt fiber and silica aerogel: the same as the steps in Example 2.

[0066] Comparative Example 3:

[0067] A method for enhancing the interfacial compatibility of basalt fiber aerogel, comprising:

[0068] Step 1: Preparation of interface modifier: the same as the steps in Example 2.

[0069] Step 2: Basalt fiber modification: the same as the steps in Example 2.

[0070] Step 3: Magnetron sputtering: First, place the modified basalt fiber in step 2 into the vacuum chamber of the magnetron sputtering equipment. The magnetron sputtering target is Ti. Vacuum the chamber to a vacuum degree of 4x10 -3 Pa; then, argon gas was introduced into the vacuum chamber, and the magnetron sputtering equipment was turned on for magnetron sputtering, wherein the substrate temperature was 350°C, the bias voltage was -150V, and the magnetron sputtering parameters were: target sputtering power 85W, working gas pressure 0.35Pa, and sputtering time 35min; finally, the magnetron sputtering was completed, and the fibers after magnetron sputtering were removed and stored in an oven for 10h at a storage temperature of 40°C.

[0071] Step 4: Composite of interface-modified basalt fiber and silica aerogel: the same as the steps in Example 2.

[0072] The performance tests were conducted on the basalt fiber aerogel composite materials prepared in Examples 1 to 3 and the basalt fiber aerogel composite materials prepared in Comparative Examples 1 to 3, respectively. The specific performances are shown in the following table:

[0073]

[0074] It can be seen from the above table that: when the bulk density and porosity are substantially the same, the surface modification of basalt fiber by means of specific interface modifier and magnetron sputtering TiO2 can effectively improve the interface compatibility between basalt fiber and silica aerogel, thereby reducing the overall thermal conductivity of the composite material and improving the overall mechanical properties of the material (i.e., compressive strength, bending elastic modulus, etc.); while Comparative Examples 1 to 2 do not use the specific interface modifier of the present application, and Comparative Example 3 does not use TiO2 for magnetron sputtering. Therefore, compared with the composite material of the present application, the interface compatibility between basalt fiber and silica aerogel in the composite materials prepared by them is low, the bonding strength is small, and an integral material without obvious microscopic boundaries cannot be formed (thus, the synergistic effect between the two materials cannot be fully exerted), which directly affects its thermal insulation (i.e., thermal conductivity) and mechanical properties, that is, Comparative Examples 1 to 3 have higher thermal conductivity and lower mechanical properties (i.e., compressive strength, bending elastic modulus, etc.) than Examples 1 to 3.

Claims

1. A method for enhancing the interfacial compatibility of basalt fiber aerogel, characterized in that: include: Step 1, preparation of interface modifier: first, anhydrous ethanol and deionized water are mixed to obtain a modified solvent, then maleic anhydride, long-chain diaminosilane coupling agent and silane coupling agent KH550 are weighed respectively, and the modified solvent is slowly added dropwise under vigorous stirring. After the addition is completed, stirring is continued for 20 to 40 minutes until there is no obvious oily substance, thereby obtaining an interface modifier; Step 2, basalt fiber modification: First, basalt is uniformly mixed in a high-speed mixer, and basalt fiber precursor is produced on an extruder with a length / diameter ratio of 40 to 45; then, after the extruded basalt fiber precursor is cooled, it is immersed in an interface modifier for modification; then, the modified basalt fiber precursor is bundled and wound by an automatic winding machine; finally, the bundled and wound fiber precursor is dried at room temperature and then placed in an oven for drying; Step 3, magnetron sputtering: First, the basalt fiber modified in step 2 is placed in the vacuum chamber of the magnetron sputtering equipment, the magnetron sputtering target is TiO2, and the vacuum is evacuated; then, argon gas is introduced into the vacuum chamber, and the magnetron sputtering equipment is turned on for magnetron sputtering; finally, after the magnetron sputtering is completed, the fiber after magnetron sputtering is removed and placed in an oven for storage; Step 4, composite of interface modified basalt fiber and silica aerogel: first, take ethyl orthosilicate, ethanol and deionized water in a stirring bottle and stir them thoroughly to obtain a mixed solution, and then use hydrochloric acid to adjust the pH of the mixed solution to 1-2; then, weave the modified basalt fibers in step 3 and lay them in layers, and add the laid basalt fibers to the mixed solution adjusted to an acidic environment, adjust the temperature to 43-47°C, react for 0.8-1.5h, and adjust the pH to 7-8 with ammonia water to obtain a composite material wet gel; finally, pour the composite material wet gel into a mold, perform pressure filtration through a vacuum-assisted system, and then perform aging and drying to obtain a basalt fiber aerogel composite material.

2. A method for enhancing the interfacial compatibility of basalt fiber aerogel according to claim 1, characterized in that: The volume ratio of the maleic anhydride, the long-chain diaminosilane coupling agent, the silane coupling agent KH550 and the modified solvent is 1.5-2.5:1-2:1-2:98-102.

3. A method for enhancing the interfacial compatibility of basalt fiber aerogel according to claim 1 or 2, characterized in that: The volume ratio of anhydrous ethanol to deionized water in step 1 is 1:

1.

4. The method for enhancing the interfacial compatibility of basalt fiber aerogel according to claim 3, characterized in that: In the step 2, the extrusion temperature of the extruder is 180-220° C., and the extrusion speed is 90-110 rpm.

5. The method for enhancing the interfacial compatibility of basalt fiber aerogel according to claim 3, characterized in that: In the step 2, the drying temperature of the oven is 90-100° C., and the drying time is 8-10 hours.

6. The method for enhancing the interfacial compatibility of basalt fiber aerogel according to claim 1, characterized in that: The vacuum degree in step 3 is 3x10 -3 ~5x10 -3 Pa, substrate temperature is 200~500℃, bias voltage is -100~-200V; magnetron sputtering parameters are: target sputtering power is 50~120W, working gas pressure is 0.25~0.5Pa, sputtering time is 30~40min.

7. The method for enhancing the interfacial compatibility of basalt fiber aerogel according to claim 1, characterized in that: The volume ratio of the tetraethyl orthosilicate, ethanol and deionized water is 2.8-3.2:2.1-2.5:0.

1.

8. The method for enhancing the interfacial compatibility of basalt fiber aerogel according to claim 7, characterized in that: The concentration of the hydrochloric acid is 0.05-0.15 mol / L, and the concentration of the ammonia water is 0.1 mol / L.

Citation Information

Patent Citations

  • Preparation method of silicon dioxide aerogel composite material for low-temperature cold insulation

    CN104628357A

  • Preparation method of basalt fiber felt reinforced aerogel material

    CN114455934A